1997
DOI: 10.1007/s002620050357
|View full text |Cite
|
Sign up to set email alerts
|

Role of perforin, granzymes and the proliferative state of the target cells in apoptosis and necrosis mediated by bispecific-antibody-activated cytotoxic T cells

Abstract: Bispecific monoclonal antibodies (bi-mAb), directed against a tumor-associated antigen and the CD3 or CD28 antigen on T lymphocytes, induce activation of resting T lymphocytes and target-specific tumor cell lysis. We now show that both necrosis and apoptosis contribute to T-cell-mediated tumor cell destruction. Even though T cells up-regulate FAS/APO-1 expression upon bi-mAb stimulation, FAS/APO-1-mediated apoptosis does not contribute to bi-mAb-mediated destruction of Hodgkin's cells. CD8+ lymphocytes were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…This mechanism of target cell death may be especially relevant in monocytemediated ADCC 17,18 . Several investigators showed that lysis of target cells by both T-cells 19 and monocytes 20 via ADCC is associated with activation of apoptotic pathways. Paclitaxel was shown to impact on Raf-dependent tumor apoptosis that is also a signaling pathway modulated by ADCC 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism of target cell death may be especially relevant in monocytemediated ADCC 17,18 . Several investigators showed that lysis of target cells by both T-cells 19 and monocytes 20 via ADCC is associated with activation of apoptotic pathways. Paclitaxel was shown to impact on Raf-dependent tumor apoptosis that is also a signaling pathway modulated by ADCC 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular aprotinin inhibits cytotoxicity by CTL, perforin and granzyme A-transfected mast cells [20], and antibody-activated T cells [35], and inhibits enzymatic activity of puri®ed granzyme A and B in vitro [36]. Although aprotinin also inhibits other serine proteases [21], the reduction in cytotoxicity with a competitive substrate for granzyme B corroborates a role for granzyme B in the killing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Two proteins, perforin and granzyme B, are integral components of the lytic machinery of cytotoxic cells (19), and cytotoxic cells are often present in allografts that are undergoing acute rejection (25). In addition, inhibition of perforin expression by antisense perforin oligonucleotides in T lymphocytes activated in vitro results in a proportional decrease of CTL cytotoxicity in mice (1).…”
Section: Discussionmentioning
confidence: 99%